Daybreak - Alix, Adolfo Borinaga Jr ([Videoflick Productions, Inc.], 2009)
William, a pediatrician, and JP, a local boatman/tour guide, spend the night in William's resthouse in Taal trying to find words, answers, and tears to decide whether to break up of take their relationship to the next level. William, leaving his wife and finally living with JP. Memories and dreams, truths and lies, fears and desires, honesty and betrayal, a love and hate, they are all closely entwined in this night. Behind the veil of words, they become intimate, but will the light of sunrise bring this intimacy to an end? "Daybreak" invites the viewer to follow the characters in the supposed death-throes of their relationship, and their downward slide into a future deset by doubts and fears. Their final decision will clearly change their lives.